Girls who green the world : thirty-four rebel women out to save our planet - Kapp, Diana (Delacorte Press, 2022)
Profiles thirty-four female scientists, innovators, and activists working to solve the climate crisis in the areas of toxic clean-up, plastic waste, clean energy, environmental technology, and food waste and production. Discusses their backgrounds, how they became involved in climate issues, and their innovations and work.